'Steppe-ing' Out of Russia's Shadow: Russia's Changing 'Energy Power' in Post-Soviet Eurasia. Issue 9 (21st October 2022) - Skalamera, Morena
Abstract: This essay analyses the evolving character of Russia's energy relationships in the post-Soviet space by looking at the Caucasus and Central Asia. In the past, due to the historic legacy of Russia-controlled pipelines, Moscow was able to exert influence by manipulating structural asymmetries in regional natural gas value chains. This has changed with China's entry as the region's major market alternative and the breakthroughs of the global energy transition. The initial phase of Russia's declining 'energy power' vis-à-vis China in Central Asia came to an end as the Crimea crisis was unfolding, an event that has drastically changed the risk perception of Russian gas in Europe, setting off a chain of consequences that led to a re-evaluation of Russia's energy power in post-Soviet Eurasia. The essay also shows, however, that Russia maintains influence in post-Soviet Eurasia through inter-elite networks and shared concerns among hydrocarbon-exporting countries about the energy transition.